The Paternalistic-Technocratic Leadership of Kyai in Developing the Entrepreneurial Spirit of Students at the Al-Amin People's Islamic Boarding School, Sumberpucung, Malang - Wahidmurni Wahidmurni; Isroqunnajah Isroqunnajah; Mohamad Kamil Salas (DAWUH : Islamic Communication Journal, 2026)
Strengthening entrepreneurship education is an important response to global economic disruption and the challenges of the demographic bonus. In the context of Islamic boarding schools, various studies have examined managerial strategies and business unit development, but there are still limited studies that conceptually and empirically explain how the leadership of Kyai shapes the entrepreneurial identity of students, especially in free Islamic boarding schools with limited financial resources. This study aims to analyze the concept, process, and impact of the paternalistic-technocratic leadership of Kyai in developing the entrepreneurial spirit of students at the Al-Amin People's Islamic Boarding School in Sumberpucung, Malang. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using an interactive model through data reduction, data presentation, and drawing conclusions with triangulation techniques to ensure credibility. The results show that the leadership of Kyai at the Al-Amin People's Islamic Boarding School is integrative between spiritual values, paternalistic relationships, and technocratic capabilities in managing the Islamic boarding school's economic system. The process of fostering entrepreneurship takes place through role models, active participation, experiential learning, and delegation of responsibilities. The impact is the formation of the entrepreneurial character of students which includes independence, creativity, and work ethic, as well as the creation of economic independence of Islamic boarding schools. This research produces a conceptual model of the SIPEA Leadership (Spiritual-Integrative, Participatory, and Entrepreneurial Adaptive Leadership) model, a model of Kyai leadership that integrates spiritual values, paternalistic role models, participatory empowerment, and the development of entrepreneurial character in students within a free Islamic boarding school system. These findings contribute to the development of Islamic educational leadership theory and the practice of Islamic boarding school-based economic empowerment.